Efficacy of a resin-modified glass ionomer varnish in the prevention of tooth enamel demineralization around orthodontic brackets: an in vitro study - Márquez Preciado, Raúl; Guzmán Castañeda, Tania Itzel; Gutiérrez Cantú, Francisco Javier; Mariel Murg, Humberto; Ruiz Rodríguez, María del Socorro; Martínez Rider, Ricardo; Oliva Rodriguez, Ricardo; Mariel Cárdenas, Jairo (Investigación Clínica, 2018)
Abstract. The purpose of this work was to evaluate the efficacy, in vitro, of a resin-mo- dified glass ionomer varnish in the prevention of tooth enamel demineralization, around orthodontic metallic brackets. Thirty healthy premolars extracted for orthodontic reasons were selected and they were divided into two groups. In group A, a resin-modified glass ionomer varnish (Clinpro XTTM varnish) was applied on the premolar enamel surface around the metallic brackets; group B was used as a control. Both groups were subjected to 500 cycles in thermal baths, they were submerged under a lactic acid solution; then, methylene blue was applied to identify and observe the demineralization zones under a stereoscopic microscope. A lesser degree of demineralization was observed in group A in comparison to group B. A greater demineralization was observed in the cervical third of both groups, showing a significant diffe- rence (p≤0.0001). The use of a resin-modified glass ionomer cement varnish was shown to be effective in preventing demineralization on the enamel surfaces around the metallic brackets, decreasing the penetration of acid substances in vitro on the enamel of the tooth.